Influenza A Reinfection in Sequential Human Challenge: Implications for Protective Immunity and "Universal" Vaccine Development. (6th April 2019) - Memoli, Matthew J; Han, Alison; Walters, Kathie-Anne; Czajkowski, Lindsay; Reed, Susan; Athota, Rani; Angela Rosas, Luz; Cervantes-Medina, Adriana; Park, Jae-Keun; Morens, David M; Kash, John C; Taubenberger, Jeffery K
Abstract: Background: Identification of correlates of protection against human influenza A virus infection is important in development of broadly protective ("universal") influenza vaccines. Certain assumptions underlie current vaccine developmental strategies, including that infection with a particular influenza A virus should offer long-term or lifelong protection against that strain, preventing reinfection. In this study we report observations made when 7 volunteers participated in sequential influenza challenge studies where they were challenged intranasally using the identical influenza A(H1N1)pdm09 virus approximately 1 year apart. We evaluate and describe the outcomes of these 7 rechallenge participants and discuss what these results may suggest about correlates of protection and development of more broadly protective influenza vaccines. Methods: Seven participants were enrolled in 2 viral challenge studies at 7.5- to 18.5-month intervals. Both challenge studies used the identical lot of influenza A (H1N1)pdm09 virus administered intranasally. We evaluated pre- and postchallenge hemagglutination inhibition, neuraminidase inhibition, and stalk antibody titers; peripheral blood leukocyte host gene expression response profiles; daily viral detection via nasal wash; and clinical signs and symptoms. Results: At least 3 of 7 participants demonstrated confirmed laboratory evidence of sequential infection, with 5 of 7 demonstrating clinical evidence. Conclusions: The data presented in this report demonstrate that sequential infection with the identical influenza A virus can occur and suggest it may not be rare. These data raise questions about immune memory responses in an acute superficial respiratory mucosal infection and their implications in development of broadly protective influenza vaccines. Further investigation of these observations is warranted. Clinical Trials Registration: NCT01646138; NCT01971255. Abstract : Sequential influenza A challenge studies in humans demonstrate reinfection with an identical A(H1N1)pdm09 virus. This raises important questions regarding correlates of protection and vaccine development.